Using a Film Intervention in Early Addiction Treatment: a Qualitative Analysis of Process. - Bjelland, Ingerid; Johansen, Ayna; Darnell, Farnad; Brendryen, Håvar (International Journal of Behavioral Medicine, 2017)
Purpose: There is a need for knowledge about how self-help materials can be made useful in treatment for Substance Abuse Disorders (SUD), as a supplement to ongoing treatment, or as independent tools for change. Objective: In this study, we explored the use of self-help films in early addiction treatment, taking into account both patient and therapist perspectives, as well as dyadic functions. We explored how active mechanisms might be related to intervention format and implementation context. A secondary aim was to examine the potential mechanisms related to the specific content of the intervention: mindfulness and acceptance psychoeducation. Methods: A qualitative exploratory research design, including a general inductive analytic approach, constructivist grounded theory, and source triangulation features, was used to code and analyze interview material. Emerging themes were developed into concepts, and finally an operational model. Participants included 12 patients and 22 therapists, in in-/outpatient addiction clinics, all in urban areas of Norway. The purpose of the design was empirical grounding of developed concepts, to promote different potential user perspectives (patients' and therapists') and obtain process data. Results: The core concept constructed, 'Alliance as experiential process,' gives a description of the data where patients and therapists accept or reject the film as a result of an experience process conceptualized as alliance formation. The alliance process model reflects the observation that patients constructed alliances autonomously, while therapists built alliances indirectly through their patients' experiences. Conclusions: Use of a self-help film may be a helpful adjunct to face-to-face therapy for patients who create a personally meaningful attachment to the film. Mindfulness/acceptance may offer one basic framework for such connection to take place.